The succession of power and its relationship with the growth of family businesses in Peru - Cahuapaza Morales, Augusto (2023)
It is common for companies to be concerned about their operational, commercial, strategic problems, among others, but family businesses that mostly belong to the range called SMEs in Peru, have additional problems that arise from their own nature, such as the Consanguinity of partners, difficulty in decision making, vision of the future, power succession plans, among others. Therefore, it is objective to describe and then relate the factors that can influence a family business to last over time, but in particular a relevant and particular variable is addressed: the succession of power. In the present investigation, it is identified if family businesses in the Tacna region have succession plans duly communicated, if they have been executed at any time, the management of the event is evaluated to determine if having a plan contributes to that the company generates growth in sales, assets, among others, or if said management tool does not significantly influence the development of the organization. The collection of information was done through a non-probability sampling for convenience, applying the interview technique to the most representative family businesses in the Tacna region, Peru to inquire about their growth, plans, goals and how they have faced or will face the power succession process. Finally, it is determined that in the present geographical area the existence of a planned succession does not have a relevant influence on the development of the companies studied.